O papel da laparoscopia diagnóstica em casos de dor abdominal inespecífica - Sales, Barion Santos Baroni (Universidade Federal do Tocantins, 2022)
Difficult to diagnose abdominal pain is a challenge in the daily routine of surgeons, however, with the popularization of access to laparoendoscopy, the surgeon has acquired another piece of the diagnostic arsenal, this one with the benefit of having a therapeutic nature. This paper aims to report the case of a patient who was admitted to the Unimed Hospital in Palmas - Tocantins, with acute abdominal pain difficult to diagnose, in which diagnostic laparoscopy was essential for detecting and surgically treating the cause. In the case report, a 22-year-old male patient presented with acute abdominal pain in the right flank and right iliac fossa, with a 7-day evolution and associated with anorexia, asthenia and prostration. No changes in laboratory tests. Computed tomography performed showed mild peritoneal thickening in the right flank and right iliac fossa. The patient was surgically approached laparoscopically, where a tumor in the parietal peritoneum was identified on the right flank, which was duly resected. The anatomopathological study identified the tumor as a necrotic lipoma. Acute abdomen is usually a very common surgical emergency that, if ignored, can lead to death. The patient in question, despite not having presented a classic clinic, had his abdominal pain complaint duly valued, thus avoiding an unfavorable evolution with a worse prognosis, demonstrating the importance of diagnostic laparoscopy in the management of patients with nonspecific abdominal pain.